1984
DOI: 10.1148/radiology.150.3.6695070
|View full text |Cite
|
Sign up to set email alerts
|

Kidney length correlated with age: normal values in children.

Abstract: Normal kidney length was measured on the excretory urogram in 262 children 0 to 14.5 years of age (422 kidneys). While mean values were similar to those in the literature, the standard deviation (0.785 cm) was much lower than that reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Examples of such conditions include Beckwith-Wiedmann syndrome, renal vein thrombosis and infant of diabetic mothers 13,14,15 . Studies on kidney size in neonate are abundant in literature, but this cannot be true in our environment 8,16,17,18 . In our study length(mm) of right and left kidney was found 39.22±4.32 and 38.36±4.30 mm respectively which is some what lower than the study of Mesrobian and coworkers 8 , Adeyekunn and co-worker 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such conditions include Beckwith-Wiedmann syndrome, renal vein thrombosis and infant of diabetic mothers 13,14,15 . Studies on kidney size in neonate are abundant in literature, but this cannot be true in our environment 8,16,17,18 . In our study length(mm) of right and left kidney was found 39.22±4.32 and 38.36±4.30 mm respectively which is some what lower than the study of Mesrobian and coworkers 8 , Adeyekunn and co-worker 19 .…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of some studies on kidney sizes in neonate among Caucasians 6,7,8 and Asians 9 . However, reports of similar studies are scant in our country.…”
Section: Introductionmentioning
confidence: 99%
“…Based on extensive experience from previous reports,7–9 kidney length is considered the best assessment tool of the size and growth of the kidneys. Our results for 43 children with BWS revealed a linear relationship between the length of the kidney and patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Renal dimensions have been measured most often on excretory urograms [3,4]. Recently, sonography has been used for the evaluation of renal dimensions [5][6][7].…”
Section: Discussionmentioning
confidence: 99%